We know the derivative of ex, which is ex.
(ex)' = ex
We can find the derivative of esinx using chain rule.
If y = ecotx, find ᵈʸ⁄dₓ.
y = ecotx
Let t = cotx.
Then, we have
y = et
Now, y = et and t = cotx. That is, y is a function of t and t is a function of x.
By chain rule, the derivative of y with respect to x,
Substitute y = et and t = cotx.
Substitute t = cotx.
Kindly mail your feedback to firstname.lastname@example.org
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
May 26, 23 12:27 PM
May 21, 23 07:40 PM
May 20, 23 10:53 PM